2021
DOI: 10.21608/jabps.2021.57135.1116
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis of volatile oil and fatty acids composition of Abutilon hirtum (Lam.) Sweet leaves

Abstract: The Volatile oil of Abutilon hirtum (Lam.) Sweet leaves extracted by a Clevenger approach and the fatty acid content of this species as a result of petroleum ether extraction were investigated using gas chromatography-mass spectrometry (GC-MS) technique. GC-MS analysis of the volatile oil revealed the presence of 63 compounds, with (2E,6E)-farnesol (6.56%), E-caryophyllene (4.68%), caryophyllene oxide (4.37%) and β-copaen-4-α-ol (3.51%) as the major components. On the other hand, 8 fatty acids of which three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A previous study [ 51 ] suggested that a decrease in MI to 20% induces sublethal effects on the test organisms, but a reduction in concentration to 50% causes fatal effects on the test organisms [ 52 ]. The inhibition of the division rate may be revealed by the phytochemical content of A. hirtum , such as phenolic acids, flavonoids, alkaloids, triterpenes, coumarins, sterols, iridoids, and essential volatile oils [ 19 , 53 ]. An interesting suggestion is that methoxyacetic acid (a part of one of these components) interferes with the metabolic pathways in the cell, resulting in cellular damage and cell abnormalities during cell division [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 51 ] suggested that a decrease in MI to 20% induces sublethal effects on the test organisms, but a reduction in concentration to 50% causes fatal effects on the test organisms [ 52 ]. The inhibition of the division rate may be revealed by the phytochemical content of A. hirtum , such as phenolic acids, flavonoids, alkaloids, triterpenes, coumarins, sterols, iridoids, and essential volatile oils [ 19 , 53 ]. An interesting suggestion is that methoxyacetic acid (a part of one of these components) interferes with the metabolic pathways in the cell, resulting in cellular damage and cell abnormalities during cell division [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid composition analysis was conducted using GC-MS on wild type and mutant 1. The identification of fatty acids relied on retention time and mass spectrum characteristics with the method proposed by Gomaa et al (2021). From the analysis, various fatty acids were successfully detected, and a comparison between the wild-type and the mutant can be made based on the total detected fatty acids.…”
Section: Lipid Composition In Wild Type and Mutantsmentioning
confidence: 99%